Pengaruh Ukuran Perusahaan, Rasio Common Size Piutang, dan Pertumbuhan Pendapatan Terhadap Durasi Audit Perusahaan Jasa - Ricky Bryan D.P Tampubolon; Mutiara Afif Andiani; Muhammad Erlangga Sumakir; Yera Hardiansyah; Arleta Matari Yuki (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2026)
This study aims to determine the effect of company size, accounts receivable ratio, and revenue growth on the duration of audits of service companies. The population in this study consists of service companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021-2024, and the research sample consists of 13 service companies that meet the research criteria. This study uses a quantitative method with an associative multiple regression analysis approach. The data used are financial report data from selected companies during 2021-2024, obtained through the IDX website and company websites. The variables in this study are independent variables, namely company size (X1), accounts receivable ratio (X2), and revenue growth (X3), and the dependent variable is audit duration (Y). Based on the results of data analysis and hypothesis testing, it shows that the variables of company size (X1) and common size receivables ratio (X2) have a positive and significant effect on audit duration (Y), while the variable of revenue growth (X3) has a positive but insignificant effect on audit duration (Y).